Analisis Masalah Pada Bidang Penunjang Medis dan Non Medis di Rumah Sakit Umum Daerah Sumbawa - Wiwiek Anindita Afrilyantari; Chatarina Umbul Wahyuni; Hermansyah Hermansyah (Universitas Malahayati Lampung, 2023)
ABSTRACT The Medical and Non-Medical Support Field functions to support the implementation of health services at the Sumbawa Regional Public Hospital. The performance results of all installations in this field do not meet the hospital minimum service standard target in 2021. This study aims to analyze problems in the field of medical and non-medical support at Sumbawa Regional Public Hospital in 2022. This study is an observational descriptive study conducted at Sumbawa regional public hospital on 18 July to 5 August 2022. The data comes from the Hospital minimum service standards report and the results of in-depth interviews. Determination of priority problems using the CARL method. To determine the root cause of priority problems using fishbone diagrams and making alternative solutions for these problems. Results: The results of the priority problem analysis score using the Carl method showed that there were no errors in laboratory examination results (144), Leftover food that was not eaten by the patient (54), Timely maintenance of alkes did not reach the target (400), Response time for post-mortem services (16), Complete medical record filling 24 hours after completion of service (36). The root of the problem is double workload, inadequate educational background (Man), digital reports have not been stored and arranged neatly (Materials), reports are not routine, equipment conditions are difficult to detect, communication is not effective, standard operating procedures are not going well. difficult to understand (Method), many tools exceed function age (Machine), culture of neglecting tasks, high service demands (Measurement), workshop not available (Mother Nature). The priority problem is the timely maintenance of medical devices does not reach the target. Training to increase human resource capacity, change communication methods, discipline officers, improve SOPs and seek availability of workshops are some of the ways to overcome the problem of timely maintenance of medical devices. Keywords: Medical Equipment, Maintenance, Hospital ABSTRAK Bidang Penunjang Medis dan Non Medis berfungsi untuk mendukung penyelenggaraan pelayanan kesehatan di RSUD Sumbawa. Hasil kinerja seluruh instalasi di bidang ini belum memenuhi target standar pelayanan minimal rumah sakit pada tahun 2021. Penelitian ini bertujuan untuk menganalisis permasalahan di bidang penunjang medis dan non medis di RSUD Sumbawa tahun 2022. Penelitian ini merupakan penelitian deskriptif observasional yang dilakukan di RSUD Sumbawa pada tanggal 18 Juli sampai dengan 5 Agustus 2022. Data berasal dari laporan standar pelayanan minimal RS dan hasil wawancara mendalam. Penentuan prioritas masalah menggunakan metode CARL. Untuk menentukan akar penyebab masalah prioritas menggunakan diagram tulang ikan. Hasil skor analisis prioritas masalah dengan metode carl menunjukkan bahwa tidak adanya kesalahan pemeriksaan hasil laboratorium (144), Sisa makanan yang tidak termakan oleh pasien (54), Ketepatan waktu pemeliharaan alkes tidak mencapai target (400), Waktu tanggap pelayanan pemulasaran jenazah (16), Kelengkapan pengisian rekam medik 24 jam setelah selesai pelayanan (36). Akar permasalahannya adalah beban kerja ganda, latar belakang pendidikan yang kurang memadai (Man), laporan digital belum tersimpan dan tersusun rapi (Material), Laporan tidak rutin, kondisi peralatan sulit dideteksi, komunikasi tidak efektif, prosedur operasi standar tidak berjalan dengan baik. sulit dipahami (Method), banyak alat melebihi usia fungsi (Machine), budaya mengabaikan tugas, tuntutan layanan tinggi (Measurement), bengkel tidak tersedia (Mother Nature). Prioritas masalah adalah ketepatan waktu pemeliharaan alkes tidak mencapai target. Pelatihan untuk meningkatkan kapasitas sumber daya manusia, mengubah cara komunikasi, mendisiplinkan petugas, memperbaiki SOP dan mengupayakan ketersediaan bengkel adalah beberapa cara untuk mengatasi masalah ketepatan waktu pemeliharaan alat kesehatan. Kata Kunci: Peralatan Medis, Pemeliharaan, Rumah Sakit